INNOVATIONS IN FORMING FINANCIAL ECOSYSTEMS - KRASNOVA, Iryna; SHCHEGLIUK, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the rest of the world, up to 75% of GDP growth in the world's most developed countries, the very beginning of innovations is established. The process of promoting financial innovations is shifted by the following factors: price volatility in most sectors of the market; informational asymmetry; inconsistency of the terms of the innovation process; high risk levels - political, financial, currency; lack of innovation infrastructure; unacceptability to innovation from the side of participants in the financial market; Insufficient value for the development of the system of financial law and protection of the rights of supporters of financial services. Irrespective of the importance of innovation shifts, look at the importance of technological innovations in the field of information security and communications. The result of which was the emergence of financial ecosystems, the relevance of such research is developing.In the article, the essence and determinants of the formation of financial ecosystems are identified. On the basis of the analysis of current trends in the development of financial markets, financial innovations, which are generated by these trends, have been developed. It is undeniable that the development of the digital economy is directly strategic for the development of financial innovations. The liberalization of financial funds, in the minds of the development of the digital economy, stimulated the emergence of a new type of bank development, with new business models that are based on a single platform of the financial market. It has been announced that the fintech industry is investing first for everything in the development of the financial market infrastructure, five fintech clusters have been seen. Promoted directly to the development of securitization of assets. It is emphasized that the formation of eco-system financial innovations should be set before the regulatory authorities for the promotion of such innovations and the development of digital technologies
Keywords: financial innovations; ecosystem; digital economy; financial infrastructure; bank; neobank; securitization